Review - Hyder, Rehan (Soundtrack, The, 2012)
Abstract In the Field: The Art of Field Recording, Cathy Lane and Angus Carlyle (2013) Axminster: Uniform Books. 240 pp., ISBN-10: 0956855962, ISBN-13: 978-0956855961 p/bk, £12.00
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9zdC41LjIuMTg5XzU